Classification of critical success factors for reverse logistics implementation based on importance-performance analysis. (2018) - Panjehfouladgaran, Hamidreza; Shirouyehzad, Hadi
Reverse logistics (RL) is one of the manufacturing methods applied to recover used products; and return them back to the process of consumption in terms of decreasing wastes and landfills. Recovered products which are the outcomes of the RL are competing with new products in the market. This competition motivates RL companies to understand about critical success factors (CSFs). Critical success factors may help RL companies to identify the strengths and stimulate customers to buy recovered products. CSFs are identified in limited researches but classification of CSFs in RL is still unexplored. In this paper, identified CSFs are classified by importance-performance analysis (IPA) in four quadrants. The importance level of the CSFs was collected based on the previous research by Panjehfouladgaran et al. (in press) and performance level by a checklist in a RL company. The results indicate that transportation, culture, organisational strategy, top management commitment and logistics network design are critical success factors that must be focused for the organisational goals achievements in RL organisations.